(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1999)
Considering Hegel’s idea of surmounting “reflexive understanding” for a process of integration in objectivity, that is, the concept of reality that underlies the knowledge constitutes a whole in immensity and, in a similar way, it is possible to accomplish and understanding of human condition as an indivisible whole; therefore, we may use Malinowski’s idea from Magic, science, and religion in an attempt of integration to reach what Hegel calls “pure science”